2021
DOI: 10.1007/s00449-021-02650-3
|View full text |Cite
|
Sign up to set email alerts
|

Genipin-crosslinked chitosan/alginate/alumina nanocomposite gels for 3D bioprinting

Abstract: Immobilizing microorganisms inside 3D printed semi-permeable substrates can be desirable for biotechnological processes since it simplifies product separation and purification, reducing costs, and processing time. To this end, we developed a strategy for synthesizing a feedstock suitable for 3D bioprinting of mechanically rigid and insoluble materials with embedded living bacteria. The processing route is based on a highly particle-filled alumina/chitosan nanocomposite gel which is reinforced by (a) electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Finally, by analyzing the most recent literary sources, it was possible to list the main challenges that stand in the way of the development of BNM technology: (i) there remains much room for the improvement of BNMs in terms of their stability and biocompatibility since BNMs have been used only in animal studies, but they have not been widely used in clinical practice [ 22 ]; (ii) understanding the energetic contributions that rule interactions at the nano–bio interface (i.e., where NPs meet biological barriers, specifically cell membranes) is very complex due to the high compositional heterogeneity of biomembranes and the intrinsic variability of the biological environment [ 34 ]; (iii) the clinical application of BNMs encounters complex fabrication processes, unsuitable large-scale production, low yields, and difficult preservation [ 24 ]; (iv) the utilization of biosynthesis (e.g., engineered bacteria) requires scaled-up manufacturing, dose determination, and potential biosafety studies [ 23 ]; (v) the processing of biomaterials (e.g., bioprinting) that incorporate living cells is still very challenging, especially considering that the production of mechanically rigid and insoluble substrates usually requires nonbiocompatible processes, such as chemical cross-linking or sintering [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, by analyzing the most recent literary sources, it was possible to list the main challenges that stand in the way of the development of BNM technology: (i) there remains much room for the improvement of BNMs in terms of their stability and biocompatibility since BNMs have been used only in animal studies, but they have not been widely used in clinical practice [ 22 ]; (ii) understanding the energetic contributions that rule interactions at the nano–bio interface (i.e., where NPs meet biological barriers, specifically cell membranes) is very complex due to the high compositional heterogeneity of biomembranes and the intrinsic variability of the biological environment [ 34 ]; (iii) the clinical application of BNMs encounters complex fabrication processes, unsuitable large-scale production, low yields, and difficult preservation [ 24 ]; (iv) the utilization of biosynthesis (e.g., engineered bacteria) requires scaled-up manufacturing, dose determination, and potential biosafety studies [ 23 ]; (v) the processing of biomaterials (e.g., bioprinting) that incorporate living cells is still very challenging, especially considering that the production of mechanically rigid and insoluble substrates usually requires nonbiocompatible processes, such as chemical cross-linking or sintering [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“… Classification of biomimetic nanomaterials (BNMs) based on the literature data, including information on biomimetic structure [ 16 , 34 , 35 , 36 , 37 , 38 ], biomimetic synthesis [ 32 , 39 , 40 , 41 , 42 , 43 ], biogenic components [ 31 , 33 , 44 , 45 , 46 , 47 ], magnetic BNMs [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ], metal and metal oxide BNMs [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ], organic, ceramic and hybrid BNMs [ 62 , 63 , 64 , 65 , 66 , 67 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…7 Mainardi et al synthesized gels using CHalginate polyelectrolyte complex with alumina nanoparticles, followed by covalent cross-linking using genipin. 8 Marapureddy et al have reported the preparation of CH-based hydrogels by carbamoylation using potassium cyanate (KCNO), which replaces the free amine in CH with a carbamyl group and induces hydrogen bonding to form a 3D network. 9 While CH has proved to be an excellent candidate in biological applications, pure CH-based materials are limited to being used as standalone scaffolds because of their low mechanical strength and stability.…”
Section: Introductionmentioning
confidence: 99%
“…CH can be functionalized to synthesize cross-linked networks using quarterization, N-acylation, oxidation, or cross-linking reactions . Mainardi et al synthesized gels using CH-alginate polyelectrolyte complex with alumina nanoparticles, followed by covalent cross-linking using genipin . Marapureddy et al have reported the preparation of CH-based hydrogels by carbamoylation using potassium cyanate (KCNO), which replaces the free amine in CH with a carbamyl group and induces hydrogen bonding to form a 3D network …”
Section: Introductionmentioning
confidence: 99%